The Catholic Teacher: Our Greatest Resource - Mussio, JCD, John King (Catholic Education: A Journal of Inquiry and Practice, 2001)
The 56th annual meeting of the National Catholic Educational Association was held in Atlantic City, New Jersey, in 1959. The following essay is a transcript of a talk delivered at that meeting on March 31, by the then Bishop of Steubenville, Ohio, the Most Reverend John King Mussio. He was speaking to the Secondary School Department about the importance of Catholic high schools and the vital role of teachers in the education and formation of youth. Although over 40 years have passed, Mussio cites many problems and challenges facing Catholic educators that are still with us today. His praise of teachers is almost poetic; his love of Catholic education is profound. Calling teachers the fifth mark of Church, Mussio clearly values the Catholic school system and those whose example and teaching help youth “to keep in step with Christ.”